A "turn-on" fluorescence sensor for ascorbic acid based on graphene quantum dots via fluorescence resonance energy transfer. Issue 6 (25th January 2018) - Gao, Yue; Yan, Xiaolu; Li, Meng; Gao, Han; Sun, Jing; Zhu, Shuyun; Han, Shuang; Jia, Li-Na; Zhao, Xian-En; Wang, Hua
Abstract : For the first time, a FRET nanosensor for AA was developed using GQDs as the energy donors and SQA-iron(iii ) as the energy acceptors. Abstract : A novel turn-on fluorescent sensor for the detection of ascorbic acid (AA) has been developed based on the fluorescence resonance energy transfer (FRET) between graphene quantum dots (GQDs) and squaric acid (SQA)-iron(iii ). In this assay, iron(iii ) can rapidly coordinate with the SQA to produce SQA-iron(iii ). The absorbance band of SQA-iron(iii ) could be largely overlapped with the emission band of GQDs, thus resulting in the fluorescence resonance energy transfer (FRET)-induced fluorescence quenching of GQDs. Moreover, the fluorescence of GQDs can be sensitively turned on by AA through the oxidation-reduction between iron(iii ) and AA. After the transformation of SQA-iron(iii ) to SQA-iron(ii ), because the absorbance of the solution reduces, the FRET decreases. This FRET-based nanosensor shows high selective and sensitive response in the concentration of AA ranging from 1.0 to 95 μM with the detection limit as lower as 200 nM, which is lower than that of other fluorescent assays. Finally, the proposed sensing system was successfully applied to the direct analysis of AA in the real samples with satisfactory results.